Art education in the XXI century: modern trends, tendency and challenges (on Kazakhstan examples) - Кожагулов, А.; Чжэнхуй, В.; Мелдеш, Г. (Культурное наследие Сибири, 2021)
Since joining UNESCO on 22 may 1992, Kazakhstan has pursued an active policy of strengthening cooperation with this international organization. During this time, Kazakhstan has become a party to many of its international conventions, including the 2003 Convention for the safeguarding of the intangible cultural heritage. The purpose of this article is to clarify the role functions of women in the preservation and promotion of the intangible cultural heritage of Kazakhstan in formal and non-formal art education on the example of women’s crafts. The authors analyzed foreign and domestic scientific and pedagogical literature in the field of integration of intangible cultural heritage and art education. In addition to the study of scientific and pedagogical theory, the study was based on the analysis of the practice of Kazakhstan’s formal and non-formal art education in the context of which the materials were collected.